Peru : Institutional and Financial Framework for Development of Small Hydropower - World Bank (Washington, DC, 2017)
Peru is favored by a stable and growing economy and the availability of indigenous sources of energy for electricity generation, hydro and natural gas. Installed capacity in Peru in 2006 was 6658 MW, of which 48 percent was hydro-based. However, regarding new investment in generation, there is reason for concern. Demand growth over the past five years has been 5-10 percent, with no signs of slowing down. At the rate of 10 percent demand growth, 400 MW of new generation capacity is necessary each year, representing at least US$250 million annually of new investment. The present study on small hydropower contains the following sections: (i) introduction; (ii) technical potential for development of small hydropower in Peru; (iii) economic and financial viability of small hydro development in Peru; (iv) institutional and regulatory environment; (v) identification of barriers to small hydropower development and mitigation measures; (vi) international experience with small hydropower development; (vii) the potential impact of the Renewable Energy Decree; and finally, (vii) conclusions and recommendations.